Stres pada Siswa Madrasyah Aliya “B” di Mariana Kabupaten Banyuasin - Santi Rosalina; Heriziana. Hz (Jurnal Kesehatan Amanah, 2024)
Basic Health Research Data (Riskesdas) in 2018, the prevalence of adolescents aged >15 years who experience emotional disorders in the form of stress, depression and anxiety disorders reached 9.8% (Ministry of Health of the Republic of Indonesia, 2018) . The large number of academic assignments makes students have to work on these assignments until late at night and become tired and sleepy in class. This causes students to be lazy to study and less able to concentrate on lessons in class. Students also often feel anxious during exams and are afraid of lowering their grades . This study aims to obtain a description of academic stress and the characteristics of students at Madrasah Aliyah "B" in Mariana, Banyuasin Regency. This study is a descriptive study, which was conducted at Madrasah Aliyah "B" in Mariana, Banyuasin Regency . The study population was all students at Madrasah Aliyah "B" totaling 80 students so that respondents were taken using the total population method. Data collection was carried out using the DASS 42 questionnaire (Depression Anxiety Stress Scales 42). The DASS 42 questionnaire used in this study will only measure stress levels through 14 statements. The measurement results will be grouped into stress (>15) and non-stress (0-14). Data analysis used in this study is univariate analysis to obtain an overview of the distribution and proportion of all variables studied. The results of the study showed that the majority of respondents were male 41 students (51.25%), the highest age was 17 years (36.25%). Almost all of the respondents' parents worked as daily laborers (66.25%), lower middle socioeconomic status (58.75%), parents' education was junior high school/equivalent (65%), did not have conflict with family (86.35%). Students who experienced stress were 45 people (56.25%), male 53.33%, 17-year-old age group 57.7%, came from families with lower middle economic status 68.8%, did not have family conflict 51.1% and parents' education < junior high school as much as 71.1%. An emotional approach to teenagers by providing more attention and spiritual education to prevent stress in teenagers.